2018
DOI: 10.1016/j.pmedr.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) types prevalence in cervical samples of female sex-workers on Curaçao

Abstract: Sex-workers have an increased risk for high-risk HPV(hrHPV) cervical cancer. On Curaçao, legal and illegal prostitution practice is high and the promiscuous lifestyle is common. We aimed to gain insight in HPV-genotype prevalence in cervical scrapes of female sex workers (FSW) and related risk factors in comparison with women not working in the sex industry.Cervical samples were taken from 76 FSW and 228 non-FSW (NFSW) age matched controls in the period between 2013 and 2015. HPV was detected by GP5+/6+ PCR-EI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 17 publications
0
18
2
Order By: Relevance
“… Publication Year Study location Total sample size No. HPV positive Velazquez-Hernandez [ 41 ] 2019 Mexico 217 12 Diop-Ndiaye [ 42 ] 2019 Senegal 436 348 Ferre [ 43 ] 2019 Togo 310 140 Lockhart [ 44 ] 2019 Kenya 344 97 Adams [ 14 ] 2019 Ghana 100 26 Shahesmaeili [ 45 ] 2018 Iran 1318 552 Muñoz-Ramírez [ 46 ] 2018 Mexico 105 6 Hooi [ 29 ] 2018 Curaçao 76 19 Richards [ 47 ] 2018 Dominican Republic 143 62 Bui [ 48 ] 2018 Cambodia 200 94 Cameron [ 49 ] 2018 Kenya 330 97 Nasirian [ 50 ] 2017 Iran 99 7 Marra [ 51 ] 2017 Netherlands 304 238 Vorsters [ 52 ] 2016 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Publication Year Study location Total sample size No. HPV positive Velazquez-Hernandez [ 41 ] 2019 Mexico 217 12 Diop-Ndiaye [ 42 ] 2019 Senegal 436 348 Ferre [ 43 ] 2019 Togo 310 140 Lockhart [ 44 ] 2019 Kenya 344 97 Adams [ 14 ] 2019 Ghana 100 26 Shahesmaeili [ 45 ] 2018 Iran 1318 552 Muñoz-Ramírez [ 46 ] 2018 Mexico 105 6 Hooi [ 29 ] 2018 Curaçao 76 19 Richards [ 47 ] 2018 Dominican Republic 143 62 Bui [ 48 ] 2018 Cambodia 200 94 Cameron [ 49 ] 2018 Kenya 330 97 Nasirian [ 50 ] 2017 Iran 99 7 Marra [ 51 ] 2017 Netherlands 304 238 Vorsters [ 52 ] 2016 …”
Section: Resultsmentioning
confidence: 99%
“…Following abnormal cytology and HPV infection, the occurrence of cervical intraepithelial neoplasia (CIN) 1, CIN 2, or CIN 3 was significantly higher among FSWs compared to the general population [ 28 ]. Thus, FSWs are thought to be at elevated risk of cervical dysplasia development due to the high HPV exposure [ 24 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following abnormal cytology and HPV infection, the occurrence of cervical intraepithelial neoplasia (CIN) 1, CIN 2, or CIN 3 was signi cantly higher among FSWs compared to the general population [28]. Thus, FSWs are thought to be at elevated risk of cervical dysplasia development due to the high HPV exposure [24,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Sex workers5 and men who have sex with men (MSM)6 7 are more exposed to the virus than other individuals in the general population and are disproportionately affected by other sexually transmitted infections (STI) 8. A higher frequency of HPV infection would be expected, and although studies have found a higher association, research has produced conflicting results 5 9–11…”
Section: Introductionmentioning
confidence: 99%
“…Sex workers constitute an epidemiologically important group for HPV infection because they may acquire this infection and transmit it to other sexual partners. However, female sex workers seem more aware of prevention strategies and more up to date on cervical cancer screening than non-female sex workers 10. It is known that the overall HPV prevalence is high in this population, affecting approximately 42.7% of female sex workers (with a range of 2.3% to 100%),12 but little is known about HPV prevalence in Brazil 13.…”
Section: Introductionmentioning
confidence: 99%